Talk Is Cheap: The Impact of Consultation. Commentary on the Article - John K Marshall (Canadian Journal of Gastroenterology)
Most recommendations for managing irritable bowel syndrome emphasize the positive roles of patient education and reassurance (1), but the impact and value of these approaches are difficult to assess. Therefore, a recent paper by Ilnyckyj et al (2) is both relevant and reassuring. This well designed study used Manitoba Health administrative databases to track health resource utilization, before and after a standardized gastroenterology consultation, by a consecutive cohort of patients with Rome I irritable bowel syndrome (IBS) attending an academic tertiary care clinic. Subjects also completed standardized survey instruments at the time of the consultation, one year and two years later to assess physical morbidity, psychological function and pain severity. During the two years of follow-up, the authors observed a reduction from baseline in the use of health resources for gastrointestinal diagnoses, but no change in consumption of resources for other indications. While pain was improved at follow-up, other measures of physical and psychological health were unchanged.